The effects of music induction on mood and affect in an Asian context - Campbell, E. A.; Berezina, E *; Gill, C. M. H. D.* (Sage, 2020)
A sample of Asian participants was assessed using the Brunel Mood Scale and the Positive & Negative Affect Scale before and after music mood induction procedures to which each participant was randomly assigned. A series of mixed analyses of variance with the type of music (happy/positive vs. sad/negative) as the between-subject factor and pre–post music exposure as the within-subject factor revealed that the sad music induction attenuated the positive moods Vigor and Happiness, as well as the negative moods Anger, Tension, Fatigue, and Confusion but had no significant impact on Depression or Calmness, casting doubt on the robustness of Thayer’s circumplex model of mood formation. The happy music induction increased Vigor and decreased Fatigue and Confusion, suggesting that positive music has the potential to lift energy levels. The happy music induction led to increases in Positive Affect only, whereas the sad music condition attenuated both Positive Affect and Negative affect, casting doubt on Watson and Tellegen’s contention that the Affect systems are independent and suggesting that the bipolarity hypothesis may not provide a comprehensive explanation of mood formation. The mechanisms by which music may impact mood and potential differences in the expression of affect between Asian and Western participants are discussed.